(untitled) (Indian Journal of Public Health Research & Development, 2021)
Background: It is estimated that poisoning accounts for over 1 million morbidities worldwide annually. Poisoning is a significant problem in rural India. The objective of this study was to understandthe pattern and demographic profile of poisoning in a tertiary care teaching hospital. Method: A retrospective cross-sectional record based study was carried out at Kamineni Institute of Medical Sciences, Nalgonda,Indiain the year 2019. Demographic details such as age, sex, type of poison consumed, route of exposure, factors affecting morbidity (need for ventilator support) and outcome of the patient were collected and documented in a structured format. Results: A total of 255 acute poisoning cases were admitted during the year 2019. The ratio of males (56.47%) and females(43.53%) was nearly 1:1. Poisoning was seen highest in the age group of 14-30 years (36%) followed by the 31-50 years age group (23.92%). The most common route of exposure was by ingestion. Overall, the mortality rate was 11.76%. The common poisonous agents consumed were insecticides(26.66%) followed by pharmaceutical products(15.68%). Conclusion: Insecticides were the most common agent for poisoning in our setting. It was found that the younger age group of 14-30 years is most vulnerable to acute poisoning and consequent mortality. Efforts should be made to create awareness and to educate the population regarding the importance of early admission and its effect on reduction in mortality. Poison-associated morbidity and mortality rates vary by region and may change over a certain period of time as new drugs and chemicals are introduced. Further studies to understand the reasons for coming into contact with poisons could possibly contribute to the prevention and early treatment of poisoning